ANALISIS PENGARUH DAYA TARIK MEDIA LUAR RUANG, POPULARITAS ENDORSER, DAN KREATIVITAS IKLAN TERHADAP EFEKTIVITAS IKLAN GUNA MENUMBUHKAN TOP OF MIND PRODUK SIMCARD GSM PRABAYAR MENTARI (Studi Kasus Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Diponeg - Rosandini, Gilar; Tae Ferdinand, Augusty (Faculty of Economics and Business Diponegoro University, 2012)
This study aims to give some answer for the problems experienced by Mentari prepaid GSM simcard Â with the decreased ranks in top of mind awareness in the public by examining the influence of outdoor media, the popularity of endorser, and creativity of advertising on the effectiveness of advertising in order to foster top of mind this product. Samples in this study are 100 people taken from the college student that use the services of mobile operators with various brands. The case study research conducted in the Faculty of Economics and Business, Diponegoro University. By using 2-stage regression with SPSS software for windows, obtained a result which indicates that the appeal of outdoor media, the popularity of endorser, and creativity of advertising have a positive and significant influence on the effectiveness of advertising in order to foster top of mind and also showed that the appeal of outdoor media have the greatest influence. Therefore, the implications suggested in this study are Indosat have to further improve the outdoor media advertising in advance so will be got great appeal in the consumerâ€™s attention and then followed by making the creative advertising and choose a popular brand endorser on that time, so a high effective advertising will appeared and top of mind will grow.